Pemanfaatan dan Pemberdayaan Pengelolaan Limbah Cangkang Lobster Air Tawar di Desa Paccellekang - Akhmad Muhammadin; Muh Akbar Nur Alief; Yudistira Y; Winda Helinda; Monica Yunais Laurensia (PT.Mantaya Idea Batara, 2022)
Pacellekang Village is located in Pattalassang District, Gowa Regency, South Sulawesi. The majority of the people in Pacellekang Village make a living as garden farmers, livestock, freshwater crayfish cultivation and daily laborers. The community's main plantation products are cassava and corn. In addition, other sources of income include chicken farming and freshwater crayfish cultivation. Several observations we made in Pacellekang Village so we chose to use freshwater lobster shell waste to increase the value of the product by processing it into wall hanging souvenirs so that it becomes a valuable value and can create jobs in the area. Another benefit of this activity is that the people in Pacellekang Village can be more creative and productive in the post-Covid-19 pandemic recovery era. In the implementation of making Lobster shell waste souvenirs through the stage of training activities to the community on how to make wall hanging souvenirs from freshwater lobster shell waste.